An alternative route of infection for viruses: entry by means of the asialoglycoprotein receptor of a Sendai virus mutant lacking its attachment protein. - Markwell, M A (1985)
During the first stage of infection, the paramyxovirus Sendai virus attaches to host cells by recognizing specific receptors on the cell surface. Productive virus-cell interactions result in membrane fusion between the viral envelope and the cell surface membrane. It has recently been shown that the ganglioside GD1a and its more complex homologs GT1b and GQ1b are cell surface receptors for Sendai virus. We report in this paper that the temperature-sensitive mutant ts271 of the Enders strain of Sendai virus lacks the viral attachment protein HN and the biological activities of hemagglutination and sialidase activity associated with it when the virus is grown at 38 degrees C. This HN- virus was unable to infect or agglutinate conventional host cells that contained receptor gangliosides and were readily infected by the parental wild-type virus. The HN- virus did, however, attach to and infect Hep G2 cells, a line of hepatoma cells that retains the asialoglycoprotein receptor (ASGP-R) upon continuous culture. This receptor is a mammalian lectin that recognizes galactose- or N-acetylgalactosamine-terminated proteins. In accordance with the known properties of this receptor, infection by the HN- virus was abolished by treatment of Hep G2 cells with sialidase, by the presence of Ca2+ chelators, and by competition with N-acetylgalactosamine, asialoorosomucoid, and antibody to the receptor. F, the only glycoprotein on the HN- virus, was shown to compete with the galactose-terminated protein asialoorosomucoid for the ASGP-R. The ability of the HN- virus to cause cell-cell fusion of Hep G2 cells indicated that attachment of this virus to the ASGP-R still permitted viral entry by its usual mode--i.e., membrane fusion at the cell surface. These results open up the possibility that enveloped viruses, which contain glycosylated proteins or lipids, may make use of naturally occurring lectins in addition to their normal receptors as a means of attachment to host cells.